The Effect of Foot Soaking in Warm Water with Galangal Mixture on Edema Foot of Third Trimester Pregnant Women in Poli Obstetry and Gynecology Rsud Dr. Hasri Ainun Habibie Gorontalo - Harismayanti Harismayanti; Ani Retni; Haslinda Damansyah (PSPP JOURNALS, 2021)
The aim of this study was to determine the effect of foot soaking in warm water with galangal mixture on edema feet of third trimester pregnant women. This type of research is an analytical survey with a research design that is true experiment design with pre-test-post-test with control group approach using purposive sampling technique with a total sample of 32 respondents. The results showed that there was an effect of foot soaking in warm water with a mixture of galangal on the edema feet of third trimester pregnant women at the Obstetrics and Gynecology Clinic, dr. Hasri Ainun Habibie Gorontalo shows that based on the alternative Wilcoxon test, the p value is = 0.001. It is recommended that the results of this study be used as input in the process of teaching and learning activities and as a reference, especially for further research.